Crafting English Domino Card (EDC) as an English Learning Media for Junior High School Students - Karisma, Yana (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2020)
Learning media is essential in making it easier for teachers to deliver learning materials. Besides, it can also ease students learning. Therefore, learning media is vital in helping the teaching and learning process. This research aimed to develop or craft English Domino Card (EDC) as English Learning Media for Junior High School Students. This research is categorized as development research or research and development (R&D). This research was used to produce products and assess product effectiveness and practicality. In relation to the design of this study, the researcher arrived at the stage of producing a product and testing its validity. Product validity testing was carried out by two experts, media experts and material experts. The results showed that English Domino Card (EDC) as an English Learning Media for Junior High School Students was very worthy. It can be seen from the expert’s judgment.